The Effect of Android-Based Test (ABT) Digital Transformation on Learning Outcomes in Fiqh Subject at MAN 3 Palembang - Lathifah; Dina Bahriani Putri; Hartatiana; Muhammad Win Afgani (The Future of Education Journal, 2026)
This study examines the limited use of digital technology in Fiqh learning at MAN 3 Palembang, where evaluation is still manual despite the implementation of Android-based exams in other subjects, leading to low student performance (41% completion rate in class XI.1). The objective of this research is to analyze the effect of Android-Based Test (ABT) digital transformation on Fiqh learning outcomes. Using a quantitative pre-experimental One-Group Pretest-Posttest Design, the population consisted of 64 students in class XI, with a purposive sample of 32 students from class XI.1 (11 male, 21 female). The instruments included a 20-item multiple-choice test on Islamic Inheritance Law, observation, and documentation. The data were analyzed descriptively (mean, SD, TSR category) and inferentially using IBM SPSS 30 (Shapiro-Wilk normality test, Levene's test for homogeneity, paired t-test). The results showed that the average pretest score was 68 (13% high, 53% moderate, 34% low), which increased to 86 in the posttest (13% high, 71% moderate, 16% low), with a significant difference (t = -9.690, sig = 0.000 < 0.05). In conclusion, ABT significantly improved Fiqh learning outcomes, recommending its routine adoption in the madrasah.